Convergence of IFRS with Local Accounting Standards: A Literature Review - Siregar, Yuliana Dewi; Aprilia, Rodiah; Kartika, Dilla Ayu; Darma, Jufri (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
Accounting is often described as the “global language of business,” as it presents financial data that is easily understood, compared, and used continuously by various parties across countries. The convergence of Indonesian Reporting Standards (IFRS) with Indonesian Financial Accounting Standards (SAK) in Indonesia is a strategic step in improving the quality of financial reporting and strengthening national economic competitiveness. However, convergence is not without challenges. IFRS implementation demands professional preparedness from accountants, auditors, and regulators because principles-based standards require careful interpretation. Furthermore, differences in Indonesia's legal and economic context necessitate certain adjustments in PSAK. This study uses a library research approach by reviewing five scientific articles published between 2020 and 2025 that are relevant to the topic of IFRS-SAK convergence. The results of the literature review indicate that IFRS convergence contributes to increased transparency, comparability, and value relevance of financial reports, primarily through the application of fair value accounting. Furthermore, convergence has been shown to suppress earnings management practices in certain sectors, particularly banking, and improve the credibility of financial reports in the eyes of global investors. However, the effectiveness of convergence is not solely determined by standards, but is also influenced by institutional factors such as corporate governance, audit quality, and regulatory consistency. This study contributes academically to enriching the discourse on the harmonization of accounting standards, and practically provides recommendations for regulators, auditors, and reporting entities in strengthening the implementation of IFRS in Indonesia.